P187 Learning-needs focused hands-on workshops on chest drain insertion and post-insertion chest drain management: how we addressed and identified patient safety issues in our hospital. (December 2018) - McDowell, K; Dissanayaka, S; Sui, S; Gavin, C; Connelly, P; Guhan, A
Abstract : Introduction: On account of its vast clinical utility, intercostal chest drain insertion (ICD-I) is an essential skill for hospital practitioners. It has been shown that adequately trained physicians can safely perform ICD-I with 3% early and 8% late complication rates howeveran unacceptably high reported rate of complications and mortality remains. The NPSA reported 12 deaths and 15 cases of serious harm related to ICD-I between 2005–2008. NHS organisations have since made efforts to improve ICD-I training for medical trainees in simulated settings (mannequin/sheep carcass). Subsequent practical training, building on these theoretical skills, remains opportunistic. In our practice, we noticed: a) Patient selection for ICD-I is often sub-optimal b) Many complications and morbidity occurs post-ICD-I, rather than during and c) Junior doctors (JD) have limited knowledge and confidence in managing chest drains post-ICD-I, especially when trouble-shooting non-functioning drains. We set out to understand the range of ICD-I and post-ICD-I management (P-ICD-I-M) skills in our hospital, and deliver hands-on workshops to address learning needs identified. Methods: Doctors of all grades and specialities in our centre were invited to complete an anonymous on-line survey. https://goo.gl/forms/c3CHq1YRn2Ua1sDs2 The results informed the programme design of five 4 hour hands-on ICD-I and post-ICD-I management workshops delivered to JD between June and December 2017. Accordingly, the focus of the workshops was weighted towards decision making (patient selection and P-ICD-I-M). We assessed our effectiveness through participants' feedback and evaluation and by repeating the on-line survey. Results: An improvement in appropriate patient selection for ICD-I occurred following attendance at workshops. 95% of delegates (n=60) answered survey questions around this theme correctly compared to 48% (n=100) pre course. Knowledge of patient management post ICD-I also improved with correct responses from 85% vs 20% of those surveyed. All trainees evaluated the course as 'excellent' overall. Conclusions: Attention generally given to technical skills' training of ICD-I, perhaps focuses less on developing, the arguably more important cognitive skills of optimal ICD-I patient selection and safe P-ICD-I-M. Our hands-on workshops addressed the identified lacunae in knowledgebase, receiving very satisfactory feedback and evaluation with demonstrably improved change in behaviour, contributing to increased patient safety.